Treatement methodes for Long QT syndrome - Ciechański, Erwin; Ciechańska, Magda; Ciechański, Krystian; Szponar, Jarosław (Journal of Education, Health and Sport, 2018)
Long QT syndrome (LQTS) is a potentially fatal cardiac disorder caused by channelopathies. Such arrhythmia is often life threatening and might cause sudden cardiac death. There are many reasons of LQTS especially: specific medications and/or electrolytes imbalance or congenital causes like Jervell and Lange-Nielsen or Romano- Ward syndromes. In recent years many ways of treatment have been developed. Except conservative treatment with B-blockers also two surgical methods improved, implantable cardioverter defibrillator (ICD) and left cardiac sympathetic denervation (LCSD). Techniques of LCSD evolved causing side effects more tolerable and lowering the risk of Horner’s syndrome. Aim of this study is to review the role of sympathectomy in LQTS.